PERSEPSI MAHASISWA KEPERAWATAN TERHADAP PEMBELAJARAN BAHASA INGGRIS DARING PADA MASA PANDEMI COVID-19 DI INSTITUT KESEHATAN DELI HUSADA DELI TUA - Sulastri Br Ginting; Tedty Rohaya Tinambunan (Jurnal Penelitian Keperawatan Medik, 2021)
The aim of the research is to determine the perception of Nursing students towards online learning in English subject during the Covid-19 Pandemic at Health Institute of Deli Husada Deli Tua Province North Sumatera 2020. The research type is a quantitative descriptive research with the method survey. The data collection technique in this study used the instrument questionnaires and data analysis techniques using descriptive statistics with percentages. The population of the research amounted to 308 students of Nursing at Health Institute of Deli Husada Deli Tua Province North Sumatera using the Proportional technique Random Sampling so that the determination of the number of samples is 15% of the total number of students This number is 47 students at Health Institute of Deli Husada Deli Tua. The validity is 0.585 and the reliability is 0.816, then the instrument in this study was declared reliable. Based on the results of the research as a whole it was concluded Nursing students' perceptions of online learning in English subjects in the Covid-19 Pandemic at Health Institute of Deli Husada Deli Tua in 2020 is in the very category positive percentage 6.38% or 3 students, positive category percentage 21.27% or 10 students, the medium category is the percentage of 42.56% or 20 students, the negative category is the percentage 23.40% or 11 students, and the very negative category the percentage of 6.38% or 3 students. So it can be said that the perception of Nursing students at Health Institute of Deli Husada Deli Tua category is medium.